Penanaman Bibit Cabai Rt 21 Rw 05 Kelurahan Betungan Kecamatan Selebar Kota Bengkulu - Yulista, Yulista; Alliyo, Aswin; Saputra, Aldi Pernandes; Amri, Bahrul; Cahyadi, Elham; Lismana, Oetari; Asnawati, Asnawati; Perdima, Feby Elra (Universitas Dehasen Bengkulu, 2025)
The 2025 Dehasen Bengkulu University Community Service Program (KKN) was held in RT 21 RW 05, Betungan Village, Selebar District, Bengkulu City. The work program implemented during the KKN period is